The Black Queer Experience Within Abrahamic Religion (American Journal of Arts and Human Science, 2024)
This paper uses a sociological perspective to examine recent religious activism for reformist narratives about racism, sexism, dualism of gender, and prejudice against transgender in the United States as signs of identity politics. Analytically, it explores how identities like race, age, class, religion, gender, and sexuality work within religious discourses, specifically regarding racism, sexism, homophobia, transphobia, and misogyny. This question leads to a consideration of America’s Original Sin, which presents the interdependency of power structures and dominance with the suppression of vindictive minorities, especially the black queer. This work aims to explore various forms of oppression intertwined in religious structures so that this study will help expose the complexity of systemic prejudice and its effects on minority populations. They emphasize the need for more discussion and representation of these topics in religious spheres and activism, calling for their recognition, acceptance, and equity. In this regard, this study seeks the following objectives: The study aims to contribute to the thematic understanding of identity, power, and oppression within contemporary religious contexts in America.